Mapping the state of financial stability - Peter Sarlin; Tuomas A. Peltonen (European Central Bank (ECB), 2011)
The paper uses the Self-Organizing Map for mapping the state of financial stability and visualizing the sources of systemic risks as well as for predicting systemic financial crises. The Self-Organizing Financial Stability Map (SOFSM) enables a two-dimensional representation of a multidimensional financial stability space that allows disentangling the individual sources impacting on systemic risks. The SOFSM can be used to monitor macro-financial vulnerabilities by locating a country in the financial stability cycle: being it either in the pre-crisis, crisis, post-crisis or tranquil state. In addition, the SOFSM performs better than or equally well as a logit model in classifying in-sample data and predicting out-of-sample the global financial crisis that started in 2007. Model robustness is tested by varying the thresholds of the models, the policymaker's preferences, and the forecasting horizons.
Keywords: E44; E58; F01; F37; G01; 330; macroprudential supervision; prediction; Self-Organizing Map (SOM); Systemic financial crisis; systemic risk; visualization